2003
DOI: 10.1039/b306437a
|View full text |Cite
|
Sign up to set email alerts
|

An extremely highly electrophilic heteroaromatic structure: 4,6-dinitrotetrazolo[1,5-a]pyridineElectronic supplementary information (ESI) available: Fig. S1 Effect of pH on the ionization of the OH group of C-4a to give the diadduct D-4a in aqueous solution. See http://www.rsc.org/suppdata/ob/b3/b306437a/

Abstract: A detailed thermodynamic and kinetic investigation of the reactions of 4,6-dinitrotetrazolo[1 ,5-a]pyridine (DNTP) with water and methanol has been made in the corresponding solvents. In aqueous solution, covalent addition of water to DNTP occurs with the exclusive formation of an anionic hydroxy sigma-complex C-4a which is half-formed in a 0.4 M HCl solution (pKa(sigma) = 0.4). This corresponds to a 3 pK-units jump in thermodynamic stability from the most stable hydroxy sigma-complex known so far, i.e. the hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 40 publications
(8 citation statements)
references
References 40 publications
2
6
0
Order By: Relevance
“…Another interesting result is the finding that nitrobenzoselenadiazole 1 b is 2 orders of magnitude more electrophilic than 1,3,5‐trinitrobenzene 8 ( E =‐13.19), the common reference aromatic electrophile in σ‐complexation processes …”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…Another interesting result is the finding that nitrobenzoselenadiazole 1 b is 2 orders of magnitude more electrophilic than 1,3,5‐trinitrobenzene 8 ( E =‐13.19), the common reference aromatic electrophile in σ‐complexation processes …”
Section: Resultssupporting
confidence: 78%
“…In an effort to obtain a quantitative measure of the reactivity of nitro derivatives of 2,1,3‐benzothiadiazole and 2,1,3‐benzoselenadiazole towards nucleophilic addition processes, we now report on the kinetic and structural analysis of the coupling reaction of 4‐nitrobenzothiadiazole 1 a and 4‐nitrobenzoselenadiazole 1 b with the reference nitroalkyl anions 2 a‐c (Scheme , Table ) in order to evaluate the electrophilic parameter E at the C‐7 position of the two electrophiles 1 a and 1 b according to Eq. (1) and to include them into the comprehensive electrophilicity scale of Mayr…”
Section: Introductionmentioning
confidence: 99%
“…As discussed in depth in previous studies of the covalent addition of water or methanol to many electrophilic Meisenheimer structures, for example, DNBF, [3] as well as to various heterocyclic cations such as the isoquinolinium or tropylium cations 10 and 11, [3,13,15,35] the observed rate constant (k obsd ) is, at a given pH, the sum of the individual first-order rate constants for formation (k f ) and decomposition (k d ) of 8 d-Me [Eq. (10)].…”
Section: à3mentioning
confidence: 99%
“…[3, 5, [13][14][15] These studies have revealed that there is a close relationship between the thermodynamic reactivity of Meisenheimer electrophiles, as measured by the related pK [Eqs. (1) and (3)] to the formation of the corresponding adducts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation